Impact of Long-Term Rice–Rice Monocropping on Soil Properties and Organic Carbon Stocks in the NSLC Command Area: A Case Study from Telangana, India - R.P. Sharma; Nirmal Kumar; K. Karthikeyan; R.K. Naitam; G.P. Obi Reddy; V. Ramamurthy; Brijesh Yadav; L.C. Malav; Abhishek Jangir; M. Nogiya; R.L. Meena; B.L. Mina; et al. (Journal of the Indian Society of Soil Science, 2025)
Soil organic carbon (SOC) is a crucial determinant of soil health and plays a vital role in climate change mitigation and sustainable agriculture, particularly in semiarid agro-ecoregions. This study evaluates the long-term impact of rice monocropping on soil properties and SOC dynamics in the Nagarjuna Sagar Left Canal (NSLC) command area of Telangana, India—an agriculturally transformed landscape that shifted from traditional rainfed cropping to canal-irrigated rice monoculture post-1967. The research aimed to characterize and classify the soils under continuous rice cultivation and to assess SOC stocks in relation to changing land use practices. A comprehensive methodology was adopted involving detailed field surveys, soil profile studies, and laboratory analyses. Four representative soil series were studied to determine physical and chemical characteristics including soil texture, pH, electrical conductivity, cation exchange capacity, and SOC content. SOC stock was estimated using standard bulk density and carbon concentration data across depth intervals. The findings revealed that long-term rice monoculture under canal irrigation significantly altered soil properties, leading to moderate alkalinity and varied SOC distribution. Notably, improved SOC stocks were observed in soils with practices such as partial residue burning, puddling, and seasonal water retention. The study highlights that despite potential SOC depletion due to intensive cultivation; appropriate management interventions can enhance carbon sequestration. The results support global initiatives like the “4 per 1000” strategy, underlining the potential of sustainable rice-based systems in enhancing SOC in hot semiarid regions. Continued research and adoption of climate-smart soil management practices are essential for improving soil health and resilience in similar agro-ecological zones.